Matematyka
nika1990
2017-06-23 19:09:35
Rozwiąż to równanie.....
Odpowiedź
milek123123
2017-06-23 19:21:11

[latex]4x^2-frac{4}{3}x+frac{1}{9}=0 \ \ (2x-frac{1}{3})^2=0 \ \ 2x-frac{1}{3}=0 \ \ 2x=frac{1}{3} \ \ x=frac{1}{6}[/latex]

Wercia495
2017-06-23 19:22:26

[latex]4x^2- frac{4}{3}x+ frac{1}{9}=0 /*9\\36x^2- frac{36}{3}x+ frac{9}{9}=0\\36x^2-12x+1=0\\Delta=b^2-4ac\\Delta=(-12)^2-4*36*1=144-144=0 [/latex] Jeżeli [latex]Delta=0[/latex] rozwiązaniem równania jest jeden pierwiastek podwójny: [latex]x_1=x_2=- frac{b}{2a}\\x_1=x_2=- frac{-12}{2*36}=- frac{-12}{72}=-(- frac{12}{72})= frac{12}{72} = frac{1}{6} [/latex] Odp. [latex]x_1=x_2= frac{1}{6}[/latex].

Dodaj swoją odpowiedź